Potential Effect of Djambal Catfish (Pangasius djambal) Gelatin as Biomaterial Product on Healing Socket after Tooth Extraction in Rats - Fredy Mardiyantoro; Nenny Prasetyaningrum; Miftakhul Cahyati; Zefry Zainal Abidin; Norifumi Nakamura (Indian Journal of Forensic Medicine & Toxicology, 2021)
Purpose: Adequate wound healing after a tooth extraction is significant because the oral cavity has amasticatory function and plays a role in nutrient intake. Various scientific studies have been conducted tofind the ideal biomaterial to support wound healing. This study aims to determine the wound healing activityusing Djambal Catfish (Pangasius djambal) gelatin after tooth extraction.Method: Gelatin was obtained from Djambal Catfish (Pangasius djambal). The sample was selected byrandom sampling, divided into 6 groups, namely the control group on the 3rd day (n=6), the control groupon the 5th day (n=6), the control group on the 7th day (n=6), the treatment group on the 3rd day (n=6), thetreatment group on the 5th day (n=6), and the treatment on the 7th day (n=6). Wound healing was examinedby evaluating wound healing marker such as macrophages, fibroblasts, epithelialization, angiogenesis, andcollagen. Data were processed using statistical analysis.Results: The treatments had a positive result in wound healing as compared with the control groups.Histological assessment showed a remarkable sign of an increased number of macrophage, fibroblast,epithelialization, and collagen deposition.Conclusion: Gelatin derived from Djambal Catfish (Pangasius djambal) can accelerate the wound healingprocess thus could be a component therapeutic potential product that may be beneficial in wound healing inthe future.